Phenotypes and genotypes in non‐consanguineous and consanguineous primary microcephaly: High incidence of epilepsy. Issue 9 (17th August 2021) - Duerinckx, Sarah; Désir, Julie; Perazzolo, Camille; Badoer, Cindy; Jacquemin, Valérie; Soblet, Julie; Maystadt, Isabelle; Tunca, Yusuf; Blaumeiser, Bettina; Ceulemans, Berten; Courtens, Winnie; Debray, François‐Guillaume; et al.
Abstract: Background: Primary microcephaly (PM) is defined as a significant reduction in occipitofrontal circumference (OFC) of prenatal onset. Clinical and genetic heterogeneity of PM represents a diagnostic challenge. Methods: We performed detailed phenotypic and genomic analyses in a large cohort (n = 169) of patients referred for PM and could establish a molecular diagnosis in 38 patients. Results: Pathogenic variants in ASPM and WDR62 were the most frequent causes in non‐consanguineous patients in our cohort. In consanguineous patients, microarray and targeted gene panel analyses reached a diagnostic yield of 67%, which contrasts with a much lower rate in non‐consanguineous patients (9%). Our series includes 11 novel pathogenic variants and we identify novel candidate genes including IGF2BP3 and DNAH2 . We confirm the progression of microcephaly over time in affected children. Epilepsy was an important associated feature in our PM cohort, affecting 34% of patients with a molecular confirmation of the PM diagnosis, with various degrees of severity and seizure types. Conclusion: Our findings will help to prioritize genomic investigations, accelerate molecular diagnoses, and improve the management of PM patients. Abstract : Phenotyping and genetic analyses in 169 probands referred for primary microcephaly produced a molecular diagnosis in 38, with ASPM and WDR62 most prevalent in non‐consanguineous patients, and a total diagnostics rate of 67% in consanguineous patients. Our series includes 11 novel pathogenic variants and reveals epilepsy as a more frequent feature than previously reported.